Serum soluble hemoglobin scavenger receptor and Sestrin 2 in fetal hypoxia of pregnant women with gestational hypertension: Serum soluble hemoglobin scavenger receptor and Sestrin 2 in fetal hypoxia of pregnant - Xie, Conghua; Liu, Qin; Wu, Wencheng; Wang, Liping; Tan, Hongyan (Journal of Medical Biochemistry, 2026)
[Objective] To assess the value of the serum levels of sestrin 2 (SESN2), heme oxidase 1 (HO-1), and soluble hemoglobin scavenger receptor (sCD163) for the prediction of intrauterine fetal hypoxia in pregnant women with gestational hypertension disorder (HDCP).[Methods] A total of 250 pregnant women with HDCP who were diagnosed and treated at this hospital from January 2023 to December 2024 were selected as the HDCP group, and 150 pregnant women with normal pregnancies who underwent prenatal examination at this hospital. Changes in the levels of serum SESN2, HO-1 and sCD163 in the two groups were observed, the levels of each index in pregnant women with HDCP of different severities were compared, and based on whether intrauterine fetal hypoxia occurred, the patients were split into two groups: those with intrauterine hypoxia and those without. The factors influencing intrauterine fetal hypoxia in pregnant women with HDCP and the predictive efficacy of serum SESN2, HO-1 and sCD163 levels for predicting intrauterine fetal hypoxia in pregnant women with HDCP were analyzed.[Results] The HDCP group had significantly higher levels of serum SESN2 and sCD163 than the normal pregnancy group (P
Keywords: Sestrin 2; Heme oxidase 1; Soluble hemoglobin scavenger receptor; Hypertensive disorders in pregnancy; Intrauterine hypoxia